Shadow banking - an assessment of measures to regulate the non-banking system - Fahrenholz, Matthias Bernhard (2019)
This study will evaluate certain proposals on banking regulation brought forward by experts in Banking and Economics and their applicability not just on traditional Banks but on Shadow Banking and the Financial System as a whole, using a scoring system. Prof. Anat Admati, Prof. John Cochrane and Jonathan McMillan (pseud.) have devised their own policy frameworks on how to regulate the Financial System in order to prevent future crises and make the system safer. Given the ongoing debates on how our financial system should be regulated it makes sense to measure how well these proposals would serve in addressing problems associated with Banking as well as Shadow Banking.